Stereotype: A Sociolinguistic Study on Freedom Writers Movie - Mukti, Vira Cahya (Prosiding University Research Colloquium, 2020)
This paper is about a sociolinguistics study of stereotypes reflected in Freedom Writers movie. The objectives of this paper is to describe the categories of stereotypes. This paper will be used descriptive qualitative method to describe the phenomenon that was happened in Freedom writers movie. The data is collected from transcript of text and dialogue from the movie. For the data analysis it will classify and interpret based on theories of sociolinguistics study. The sociolinguistics problem of stereotypes that is found from the movie are gender, race and occupation. In the movie race is the highest frequency since the character of the movie come from multicultural communities. Therefore, it is easier to identify the racist problem in the movie since there are data found.